Unexpected detection of SARS-CoV-2 antibodies in the prepandemic period in Italy. Issue 5 (October 2021) - Apolone, Giovanni; Montomoli, Emanuele; Manenti, Alessandro; Boeri, Mattia; Sabia, Federica; Hyseni, Inesa; Mazzini, Livia; Martinuzzi, Donata; Cantone, Laura; Milanese, Gianluca; Sestini, Stefano; Suatoni, Paola; et al.
There are no robust data on the real onset of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and spread in the prepandemic period worldwide. We investigated the presence of SARS-CoV-2 receptor-binding domain (RBD)–specific antibodies in blood samples of 959 asymptomatic individuals enrolled in a prospective lung cancer screening trial between September 2019 and March 2020 to track the date of onset, frequency, and temporal and geographic variations across the Italian regions. SARS-CoV-2 RBD-specific antibodies were detected in 111 of 959 (11.6%) individuals, starting from September 2019 (14%), with a cluster of positive cases (>30%) in the second week of February 2020 and the highest number (53.2%) in Lombardy. This study shows an unexpected very early circulation of SARS-CoV-2 among asymptomatic individuals in Italy several months before the first patient was identified, and clarifies the onset and spread of the coronavirus disease 2019 (COVID-19) pandemic. Finding SARS-CoV-2 antibodies in asymptomatic people before the COVID-19 outbreak in Italy may reshape the history of pandemic.